Answer:
Explanation:
By the general expresion:
T4(x) = f(a) + (f'(a)/1!)*(x-a) + (f''(a)/2!)*(x-a)² + (f'''(a)/3!)*(x-a)³ + (f''''(a)/4!)*(x-a)^4
Then:
f(x) = sinx ; f'(x) = cosx ; f''(x) = -sinx ; f'''(x) = -cosx ; f''''(x) = sinx
Since: sin(π/6) = 1/2 ; cos(π/6) =
![√(3)/2](https://img.qammunity.org/2021/formulas/mathematics/college/mecrf7ve27u9291jcnmvock0210lnlnm0e.png)
Thus, in the expresion for T4(x):
![T4(x) = 1/2 + (√(3)/2 )*(x-\pi/6) - (1/4)*(x-\pi/6)^(2) - (√(3)/12)*(x-\pi/6)^(3) + (1/48)*(x-\pi/6)^(4)](https://img.qammunity.org/2021/formulas/mathematics/college/bdqe1l8a3dhzqij7kxoxnbfv8rztl4jg18.png)
Inequality, by the Taylor's theorem (jpg adjunt):
We need to find M in the interval indicate. Of the analysis from the graf of the function (jpg adjunt), we see a good candidate is:
M = f(π/3) = sin(π/3) =
![√(3)/2](https://img.qammunity.org/2021/formulas/mathematics/college/mecrf7ve27u9291jcnmvock0210lnlnm0e.png)
Then, in the Taylor's theorem:
![|R(x)| \leq (√(3)/2)* (|x-\pi/6 |^(5) )/(5!)](https://img.qammunity.org/2021/formulas/mathematics/college/zu0q0hn72ng5g14qonsanhde6whsea43sc.png)